OP279 Monitoring The Effectiveness Of Implementing And Using New Health Technologies In Hospital Practice. (December 2020) - Avdeyev, Andrey; Benberin, Valeriy; Shanazarov, Nasrulla; Kudaibergenova, Maigul; Kaptagayeva, Aigul; Makalkina, Larissa; Hailey, David; Akhmedullin, Ruslan; Ismailova, Leilya; Nurmasheva, Arailym
Abstract : Introduction: According to international experience in the field of hospital-based health technology assessment (HB-HTA), most of the implemented new health technologies must undergo a clinical and economic assessment (CEA) of their viability by creating a mini-health technology assessment report. However, HB-HTA should not be limited only to the initial CEA; further monitoring of the effectiveness of implemented new health technologies is necessary. Methods: We developed a special reporting form for creating a CEA of implemented new health technologies and integrated it into the hospital information system. Indicators of clinical effectiveness are determined individually for each implemented technology. The main indicators of economic effectiveness are financial results (or net profit) and profitability—high-cost and high-tech health technologies have priority for monitoring. Results: In order to ensure a more detailed and complete CEA of implemented health technologies, the following measures were proposed: (i) before implementing the technology, determine the key clinical effectiveness criteria for further monitoring for each implemented health technology; (ii) if possible, determine comparative technologies (alternatives or analogs) for conducting comparative CEA of the implemented health technologies; and (iii) carry out a prospective CEA of the implemented health technologies with a view to publishing the results. Conclusions: The organization of a continuous monitoring process that analyzes the effectiveness and usage of new health technologies in hospital practice will allow assessment of the following: the clinical effectiveness and safety of the implemented technologies in comparison with world data; the economic effectiveness of the technology, including an accurate calculation of the payback period for investments; and the "real" data on the effectiveness of implemented health technologies in comparison with the initial request for implementation.